A New Species of the Deep-Sea Sponge-Associated Genus Eiconaxius (Crustacea: Decapoda: Axiidae), With New Insights Into the Distribution, Speciation, and Mitogenomic Phylogeny of Axiidean Shrimps - Kou, Qi; Xu, Peng; Poore, Gary C. B.; Li, Xinzheng; Wang, Chunsheng (Frontiers in Marine Science, 2020)
Eiconaxius Bate, 1888 is a genus of axiid shrimps exclusively associated with deep-sea hexactinellid sponges. Due to its special morphology and habitat, Eiconaxius is taxonomically and ecologically controversial. Based on material recently collected from seamounts in the northwestern Pacific, a new species of Eiconaxius is described. Intraspecific morphological and genetic variation, and host specificity were evaluated. The complete mitochondrial genome of the new species was sequenced to explore the systematic status of Eiconaxius and some other axiidean taxa. Our analyses showed that differentiation of the new species occur both allopatrically and sympatrically, probably resulting from the interaction of geographical isolation and deep water current movement, rather than from adaptation to different hosts. In addition, species of Eiconaxius are suggested to have wider ranges of distribution and host than expected. The reconstructed mitogenomic phylogeny supported merging Eiconaxius into Axiidae, and recognized most axiidean families, except that Strahlaxiidae was suggested to be paraphyletic. However, more comprehensive taxon sampling is still needed to resolve the explicit internal relationships among Axiidea.